A new concept for UAV landing gear shock vibration control using pre-straining spring momentum exchange impact damper. (April 2018) - Son, Lovely; Bur, Mulyadi; Rusli, Meifal
This study proposes a new method for reducing the shock vibration response of an Unmanned Aerial Vehicle (UAV) during the landing process by means of the momentum exchange principle (MEID). The performance of the impact damper is improved by adding a pre-straining spring to the damper system. This research discusses the theoretical application of the damper to the UAV landing gear system. The UAV dynamics is first modeled as a simple lumped mass translational vibration system. Then we analyze a more complex two-dimensional model of UAV dynamics. This model consists of the main wheel, nose wheel and main body. Three cases of UAV landing gear mechanisms: without damper, with passive MEID (PMEID) and with pre-straining spring MEID (PSMEID) are simulated. The damper performance is evaluated from the maximum acceleration and force transmission to the main body. The energy balance calculation is conducted to investigate the performance of PSMEID. The simulation results show that the proposed PSMEID method is the most effective method for reducing the maximum acceleration and force transmission of UAV during impact landing.